2019
DOI: 10.3390/molecules24020361
|View full text |Cite
|
Sign up to set email alerts
|

Solution Combustion Synthesis of Cr2O3 Nanoparticles and the Catalytic Performance for Dehydrofluorination of 1,1,1,3,3-Pentafluoropropane to 1,3,3,3-Tetrafluoropropene

Abstract: Cr2O3 nanoparticles were prepared by solution combustion synthesis (SCS) with chromium nitrate as the precursor and glycine as the fuel. Commercial Cr2O3 and Cr2O3 prepared by a precipitation method were also included for comparison. The morphology, structure, acidity and particle size of fresh and spent Cr2O3 catalysts were investigated by techniques such as XRD, SEM, TEM, BET and NH3-TPD. In addition, catalytic performance was evaluated for the dehydrofluorination of 1,1,1,3,3-pentafluoropropane (CF3CH2CHF2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…For the catalysts with moderate Lewis acidity, such as MgF 2 , SrF 2 , BaF 2 CrF 3 , and LaF 3 , although lower than that of AlF 3 , high conversion levels of HCFC-142b are obtained. It is well accepted that fluorinated Cr 2 O 3 possesses high affinity to fluorocarbons and excellent dehydrofluorination activity to hydrofluorocarbons. ,, Consequently, as indicated by the XRD pattern, although CrF 3 is partially oxidized to Cr 2 O 3 , high conversion of HCFC-142b is still approached.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the catalysts with moderate Lewis acidity, such as MgF 2 , SrF 2 , BaF 2 CrF 3 , and LaF 3 , although lower than that of AlF 3 , high conversion levels of HCFC-142b are obtained. It is well accepted that fluorinated Cr 2 O 3 possesses high affinity to fluorocarbons and excellent dehydrofluorination activity to hydrofluorocarbons. ,, Consequently, as indicated by the XRD pattern, although CrF 3 is partially oxidized to Cr 2 O 3 , high conversion of HCFC-142b is still approached.…”
Section: Resultsmentioning
confidence: 99%
“…It is well accepted that fluorinated Cr 2 O 3 possesses high affinity to fluorocarbons and excellent dehydrofluorination activity to hydrofluorocarbons. 12,13,17 Consequently, as indicated by the XRD pattern, although CrF 3 is partially oxidized to Cr 2 O 3 , high conversion of HCFC-142b is still approached.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The O 1s core-level spectrum can be decomposed into CO (531.48 eV), −OH (533.03 eV), and −COOH (535.38 eV) bonds (Figure G). The Cr 2p core-level spectrum (Figure H) of Cr 2 O 3 NPs showed that there were three different states of chromium in Cr 2 O 3 NPs, including the Cr metallic bond (574.28 eV), , CrO 3 (589.28 eV), , and Cr 2 O 3 (576.38, 577.08, 579.83, 584.38, and 586.73 eV). According to the Cr 2p signal, the ratios of Cr 2 O 3 , CrO 3 , and metallic Cr in our prepared nanoparticles were calculated to be 90.19, 5.41, and 4.40%, respectively. All of the above results indicate that the resulting nanoparticles prepared by microwave heating Cr 3+ and sodium citrate were citrate-coated Cr 2 O 3 NPs.…”
Section: Resultsmentioning
confidence: 99%
“…Dehydrofluorination of HFC‐134a known as an endothermic reaction shows considerable conversion under a high temperature, fortunately the high performance catalyst will be employed to reduce the reaction temperature and increase yield. In most of literatures, the reported dehydrofluorination catalyst were metal fluorides,, metal oxides,, pyrophosphate and carbon ,. Among these catalysts, metal fluorides are the promising catalysts in a corrosive atmosphere (HF) and elevating temperature conditions.…”
Section: Introductionmentioning
confidence: 99%